The The need analysis of PjBL Model Science e-book based indigenous knowledge on process of making ulos woven cloth - Danang Habib Pratama; Maryati Maryati; Suyanta Suyanta (Postgraduate, University of Mataram, 2023)
The need and availability of digital open materials such as e-books that contain original knowledge are very necessary in science learning, in order to create contextual learning. The basis for the need for e-books containing indigenous knowledge is the existence of various problems that occur in science learning. Some of the problems with science learning include, students still think it is difficult, science learning is irrelevant, uninteresting and monotonous, student’s comprehension ability is lacking and non-contextual science learning. This research aims to find out what needs teachers and students want so that science learning can be more innovative. This research uses descriptive qualitative methods. The instruments used were interview guides, questionnaire sheets and science literacy tests. Data collection carried out in this research was interviews, questionnaires and scientific literacy tests. The sample involved in this research was 1 teacher and 53 students using a cluster random sampling technical.